Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1007/bf00165699
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors accelerate epithelial repair in sheep trachea

Abstract: Toxic gases and fumes have been shown to be injurious to the upper airways. Repair of this injury involves proliferation and migration of surviving nonciliated cells, followed by differentiation to a normal phenotype. Because recent results suggested that growth factors could improve the outcome of an airway injury, we undertook this study to determine the efficacy of these materials as an initial treatment to accelerate the healing process. In 24 anesthetized sheep, a portion of the trachea was exposed to smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…EGF has been reported to play a major role in epithelial The differentiation of the mammalian reproductive tract into the male phenotype depends on the presence of regeneration and wound healing; it has been shown to accelerate corneal wound healing and healing of the functional testes, secreting testosterone. Of significant interest are the recent reports of Gupta et al [7,8] who intestinal mucosa and respiratory epithelial tracts in experimental animals [9][10][11][12][13][14][15][16][17]. The inadequate expression found that the masculinization of the genitourinary tract may be mediated by EGF.…”
Section: Egfr Antibody Was Replaced By Buffer In Negative Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGF has been reported to play a major role in epithelial The differentiation of the mammalian reproductive tract into the male phenotype depends on the presence of regeneration and wound healing; it has been shown to accelerate corneal wound healing and healing of the functional testes, secreting testosterone. Of significant interest are the recent reports of Gupta et al [7,8] who intestinal mucosa and respiratory epithelial tracts in experimental animals [9][10][11][12][13][14][15][16][17]. The inadequate expression found that the masculinization of the genitourinary tract may be mediated by EGF.…”
Section: Egfr Antibody Was Replaced By Buffer In Negative Controlsmentioning
confidence: 99%
“…EGF plays an essential role in the normal regeneration had penoscrotal hypospadias, who had undergone two previous procedures complicated by fistula formation. and healing of epithelial surfaces, including respiratory, gastrointestinal, genitourinary and corneal epithelia [10][11][12][13][14][15][16][17]. EGF receptor (EGFR) has been identified on Immunohistochemistry cells of various origin, including fibroblasts, corneal cells, breast cells and cells derived from some tumours Tissues were collected in normal saline, fixed in 10% formalin for 24 h and embedded in paraffin wax.…”
Section: Introductionmentioning
confidence: 99%
“…19 EGF also promotes cell survival and can protect against smoke-induced injury in vivo. 20 The mechanisms underlying the stress/repair responses after ozone exposure in vivo are not well understood. In previous studies we have shown that nasal epithelium co-expresses 3 members of the c-erbB family (EGFR, cerbB2, and c-erbB3).…”
mentioning
confidence: 99%
“…De plus, Barrow et al ont suggéré que l'EGF et le PDGF (platelet-derived growth factor) favorisent la régénération de l'épithélium respiratoire en stimulant la prolifération et la différenciation des cellules épithéliales respiratoires [38]. L'HGF (hepatocyte growth factor), le KGF (keratinocyte growth factor) et les IL-1α et β régulent la migration cellulaire, mais peuvent également avoir une action mitogénique [39][40][41].…”
Section: éTape IVunclassified